From Political Islam to Civil Religion: The Possibilities of a Pluralistic Constitution and its Impact on Human Rights in Post-Revolutionary Iran - Leila Chamankhah (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2022)
The two categories of political religion and civil (also civic) religion, and the ways a nation can nurture the latter, have been the concern of a number of philosophers since long time ago. Relevant to this is the ideals of democracy, the separation of religion and politics and the necessity of having a secular legal covenant, which represents the political philosophy of a modern republic. Theorists of civil religion, particularly Jean-Jacques Rousseau, were concerned with the role of established religions, in modern political systems and that is why they put forward different, and at times even contrasting, theories about the compatibility of Christianity as well as the objectives of modern politics, at the center of which is the ideal of citizenship. The present paper will focus on the post-revolutionary constitution as well as the legal status of republicanism to investigate the possibilities, if any, of finding a solution to the long-lasting problematic of Islam and democracy in Iran. My hypothesis is that the current constitution is incapable of allowing for democracy, and due to its monistic nature, hinders reconciliation between Islam and democracy. Iran needs a better legal covenant, one in which the legacy of republicanism, as well as religious pluralism, is respected and endorsed.